Relevansi Nilai-Nilai Moderasi Dakwah Islam di Masyarakat Kampung Arak Poncol - Ngawi - Mujab, Saiful (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2020)
This study discusses the moderation process of Islamic da'wah which puts forward a persuasive, tolerant, and cultural approach in a remote hamlet where the majority of the people are wine/arak producers. This research uses a qualitative methodology by following a constructionistic logic, namely placing the subject's relationship with the reality-in-awareness of the research subject. Reality in the awareness of this subject can start from observations, participation in interactions, in-depth dialogues, reading and so on. The results of this research can be narrowed down into three points, namely; First, Islamic da'wah with a moderate and moderate approach will minimize friction/horizontal clashes between da'i (subject of da'wah) and mad'u (object of da'wah). Second, the understanding of the local village religious leaders who are NU-style (Nahdlotul Ulama) has implications for the practice of cultural Islamic da'wah which prioritizes moderate attitudes and moderation. Third, the moderation model of Islamic da'wah in Poncol Hamlet (arak producing community) has proven to be able to consistently attract public sympathy. This is reinforced by statistical evidence of the quantity and quality of the local community's religiosity consistently.